Finite propagation speed and kernels of strictly elliptic operators. (1985) - Gurarie, David
Abstract : We establish estimates of the resolvent and other related kernels and discussL p -theory for a class of strictly elliptic operators onR n . The class of operators considered in the paper is of the formA 0 + B with the leading elliptic partA 0 and a singular perturbationB, whose coefficients haveL p -type and are modeled after Schrödinger operators.